(untitled) (Research, Society and Development, 2025)
Burnout Syndrome is recognized as one of the main psychosocial disorders affecting health professionals, particularly nurses, whose work routine is marked by emotional overload, long working hours, and high care demands. This article aims to analyze the role of nurses in the prevention and management of Burnout Syndrome in health professionals through a systematic literature review based on PRISMA 2020 guidelines. The search was carried out in the SciELO, PubMed, and LILACS databases between 2015 and 2025, using DeCS/MeSH descriptors combined with Boolean operators. The results show that nurses play a strategic role in the early identification of burnout symptoms, in the implementation of mental health promotion programs, and in the development of healthy work environments. It is concluded that strengthening institutional policies and continuing health education is essential to reduce the prevalence of the syndrome and to ensure safer and more humanized care practices.